Challenges and conservation implications of Polylepis woodlands in the Andean region: Defining actions for sustainable management - Pinos, Juan (Hacquetia, 2020)
Polylepis species represent one of the most important and endemic woodlands of the mid- and high-elevation regions of the Andean Cordillera. I provide a review of the current situation of Polylepis woodlands, discuss the potential effects of various conservation measures and consider the likely impact of climate change on tree phenology and tree regeneration, aiming to foster the conservation and sustainable management of these woodlands through proper environmental planning. I argue that in addition to the delineation and extension of protected areas, it is essential to incorporate actions such as forestation, forest policies, environmental education and local community participation. To be effective, conservation measures should be implemented in an international transdisciplinary research framework and in harmony with site-specific conditions. Finally, given the likely but uncertain influences of climate change on Polylepis woodlands, further research (and communication of that research) is needed to improve forest management strategies and research priorities for the Andean region.